STUDY ON THE INTERFACE REACTION LAYER OF DIFFUSION BONDED SIALON AND DUPLEX STAINLESS STEEL - HARIS, FARHANA (2018)
Sialon - an advanced ceramic composed of silicon, aluminium, oxygen and nitrogen, is known to have high strength and resistance towards corrosion. However, due to its brittleness, the application of this material is very limited.